Tissue-specific in vivo protein-DNA interactions at the promoter region of the Xenopus 63 kDa keratin gene during metamorphosis. - Warshawsky, D (1995)
The Xenopus 63 kDa keratin gene is developmentally regulated and is expressed only in the epidermis. Full activation of the 63 kDa keratin gene requires two regulatory steps, the first independent and the second dependent on the thyroid hormone triiodothyronine (T3). Sequence analysis of a genomic clone of the 63 kDa keratin gene identified potential AP2 and SP1 binding sites upstream of the transcription initiation site. Electrophoretic mobility shift assays using purified or enriched proteins, as well as HeLa nuclear extract in conjunction with AP2- and SP1-specific antibodies, have been used to demonstrate that human AP2 and SP1 bind elements upstream of the transcription initiation site. In vivo footprinting with ligation mediated PCR revealed several footprints, within 350 bp upstream of the transcription initiation site, including those at the AP2 and SP1 sites, that are unique to epidermal cells which express the keratin gene. These footprints were absent in blood cells and XL177 cells which do not express the gene. Comparison of footprints between cells which express the 63 kDa keratin gene at low or high levels showed that the same binding sites are occupied, indicating that these sites are required for basal as well as T3-induced expression of the 63 kDa keratin gene.